2021
DOI: 10.3389/fnagi.2021.668775
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Supplementation Facilitates Recovery of 6-OHDA-Induced Motor Deficit via Improving Mitochondrial Function and Energy Metabolism

Abstract: Parkinson’s disease (PD) is a neurodegenerative disease associated with progressive impairment of motor and non-motor functions in aging people. Overwhelming evidence indicate that mitochondrial dysfunction is a central factor in PD pathophysiology, which impairs energy metabolism. While, several other studies have shown probiotic supplementations to improve host energy metabolism, alleviate the disease progression, prevent gut microbiota dysbiosis and alter commensal bacterial metabolites. But, whether probio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…Moreover, probiotics can generate antioxidant metabolites, such as glutathione [ 45 ], folate [ 47 ], and butyrate [ 46 ]. In this study, our probiotic/prebiotic treatments directly increased the activity of host antioxidant enzymes, in accordance with previous studies [ 38 , 48 , 49 ]. Furthermore, Romo-Araiza et al [ 49 ] reported that probiotic, prebiotic, and synbiotic supplementation could suppress the levels of the pro-inflammatory cytokines IL-1β and TNF-α.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, probiotics can generate antioxidant metabolites, such as glutathione [ 45 ], folate [ 47 ], and butyrate [ 46 ]. In this study, our probiotic/prebiotic treatments directly increased the activity of host antioxidant enzymes, in accordance with previous studies [ 38 , 48 , 49 ]. Furthermore, Romo-Araiza et al [ 49 ] reported that probiotic, prebiotic, and synbiotic supplementation could suppress the levels of the pro-inflammatory cytokines IL-1β and TNF-α.…”
Section: Discussionsupporting
confidence: 93%
“…Improved host antioxidant activity and reduced oxidative stress may also play roles in the suppression of TNF-α observed in this study. Additionally, the antioxidant and anti-inflammatory effects conferred by the probiotic and its residual medium may further prevent deleterious changes in mitochondrial function, as we described previously [ 38 ]. Overall, our results indicated that the probiotic, its medium residue, and the cocktail prevented the vicious cycle of mitochondrial dysfunction, oxidative stress, and inflammation in the rat model of PD, and these supplements eventually improved motor function and restored dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations